Lebenswelt, Leiblichkeit und Resonanz: Eine raumphänomenologisch-rekonstruktive Perspektive auf Geographien der Alltäglichkeit - T. Dörfler; E. Rothfuß (Geographica Helvetica, 2018)
This article aims to explore the potential of Alfred Schütz' sociological phenomenology for spatial phenomena and its integration into human geography. Although the influence and productivity of phenomenology in general could contribute significantly to shed light on spatial phenomena of the life-world, such as a progressive sense of place (Massey, 1993), transnationalities (Pries, 2001), socio-spatial atmospheres (Hasse, 2017), “home” and encounters (Seamon, 1979, 2014), enforced life(s) in refugee camps and others, it has never become a major strand of contemporary (German speaking) human geography. According to Hasse (2017) phenomenology has even remained almost absent in geographical research. In contrast to this proposition, the analytically endorsed and empirically examined theorems of phenomenology have recently been challenged by “post-phenomenology” and “non-representational theory”. These approaches raise – though both argumentatively and empirically unproven – their voice against pretended limitations of “classical” phenomenology in arguing with “imagined” limits of meaning and understanding. Irrespective of these developments, we would like to refer to the analytical and methodological stringency of approaches that arise from the rich tradition of phenomenology and emphasize their still largely untapped potential for human geography by suggesting a “Leib”-based approach rooted in reconstructive methodologies to analyse the various spatial phenomena of the life-world.